Electoral bias at the 2015 general election: reducing Labour's electoral advantage. Issue 4 (1st October 2016) - Thrasher, Michael; Borisyuk, Galina; Rallings, Colin; Johnston, Ron; Pattie, Charles
ABSTRACT: Electoral bias results in an asymmetrical seat distribution between parties with similar vote shares. Over recent British general elections Labour held an advantage because it efficiently converted votes into seats. Following the 2015 election result this advantage has reduced considerably, principally because Labour's vote distribution saw it accumulate more ineffective votes, particularly where electoral support was not converted into seats. By contrast, the vote distribution of the Conservative party is now superior to that of Labour because it acquired fewer wasted votes although Labour retains a modest advantage overall because it benefits from inequalities in electorate size and differences in voter turnout. Features of the 2015 election, however, raise general methodological challenges for decomposing electoral bias. The analysis, therefore, considers the effect of substituting the Liberal Democrats as the third party with the United Kingdom Independence Party. It also examines the outcome in Scotland separately from that in England and Wales. Following this analysis it becomes clear that the method for decomposing electoral bias requires clearer guidelines for its application in specific settings.